Phytochemical, nutritional and antioxidant capacity of five Ivorian edible leaves aqueous extracts - Marcel Koffi Konan, Emmanuel N’Dri Koffi & , Ibrahima Cisse, Augustin Amissa Adima, Yves-Alain Bekro (Journal of Applied Pharmaceutical Science, 2016)
Boiled aqueous extract from five Ivorian edible leaves (Solanum scabrum, Ipomea batatas, Corchorus olitorius, Basella alba, Hibiscus sabdariffa) have been analyzed for their antioxidant contents, phytochemical and nutritional compositions. I. batata extract showed the highest amount of antioxidant (167.52 µg/100gTE), total polyphenol (34.18 mg/100 g TE) and total flavonoid (12.67 mg/100g TE). The higher energy value (225.5 kcal) was obtained in S. scrabrum extract. The highest amount of zinc and potassium were found in S. scrabrum extract (0.28 and 362.1 mg/100 g DW; respectively). Maximum amount of copper (1.16 mg/100 g DW) and calcium (777.9 mg/100 g DW) were obtained in H. sabdariffa extract. The highest content of iron (49.81 mg/100 g DW) and magnesium (201 mg/100 g DW) were observed in B. alba extract. The highest content of sodium (2.39 mg/100 g DW) was obtained in C. olitorius extract. All extracts contained secondary metabolites such as polyphenols (tannins, flavonoids), sterols and terpenes, which have medicinal potent.
Keywords: Edible leaves, antioxidant, phytochemical and nutritional compositions.